Preparation and Physico-Chemical Properties of Polypropylene and Oil Palm Empty Fruit Bunch Fibre Composites - Hashim, Norazlina (2008)
Composites of polypropylene (PP) and oil palm empty fruit bunch (OPEFB) were prepared by melt blending, and the effects of ethylene-butene copolymer (EBNR) as an impact modifier, on the mechanical and thermal properties of OPEFB:PP composites were investigated by using FTIR, DSC, TGA and SEM. Composites were prepared at 10, 20, 30, 40, 50 and 60% by weight of fibre. Different fibre loading, temperatures, rotation time and rotation speeds were tested to determine the optimum condition of blending. Two range sizes of fibre were used in this study and there are below 200 μm and between 200-315 μm of length (known as 200 μm and 315 μm). The study was mainly conducted on composite with 20% and 40% fibre loading. The optimum temperature and reaction period for blending OPEFB with PP were 170oC and 10 minutes with rotation speed at 50 rpm, respectively. The result from FTIR analysis indicated that the interaction is only physical between the components of the composite. Tensile tests on the composites showed that EBNR had a positive effect on the elongation at break and negative effect on tensile modulus, but no improvement on tensile strength. This impact modifier was found to decrease the stiffness of the composites. The impact strength was improved in addition of EBNR, but for flexural test, no significant effect was observed. The increasing in impact strength was shown for both notched and unnotched samples starting from 1% of EBNR loading but they reduced when it reached at optimum volume. Smaller fibre size, 200 μm gave higher impact strength compared to 315 μm. The presence of EBNR on the composite made a weak improvement in thermal stability as shown by thermogravimetric analysis (TGA). DMA studies established that the EBNR led to reduction of stiffness and enhancing mobility of the resulting composite. The surface morphology showed less void in EBNR composites where OPEFB fibre seems to be covered with a smooth layer of EBNR. The environmental degradation behaviour on the physical and mechanical properties of OPEFB:PP composites has been studied with special reference to the influence of ageing conditions like treatment with water, soil degradation, and chemical resistance. With the increased of fibre loading, the water absorption was also increased, and the addition of EBNR led to less water absorption, and the lowest absorption was observed for 8% EBNR loading. Tensile properties decrease with water uptake and time of immersion. The effect of alkaline (0.5M NaOH) and acidic (0.5M HCl) solutions on the composites were investigated in a period of one month. The results showed the decreasing in tensile strength and mass. Temperature dependence studies were also conducted at different temperature, 25oC, 45oC and 75oC, and found that the degradation was faster at higher temperature. The biodegradability of composites was evaluated by the soil-burial test in six months. The mass of composites slowly showed the decreasing after that time as expected.